African marine invertebrate data analysis and imaging: a dataset and digital platform for research, education and outreach - Niza, Henrique Martins Espada (2019)
Tese de mestrado, Bioinformática e Biologia Computacional, Universidade de Lisboa, Faculdade de Ciências, 2019